2011
DOI: 10.1115/1.4003055
|View full text |Cite
|
Sign up to set email alerts
|

Aerothermal Performance of a Winglet at Engine Representative Mach and Reynolds Numbers

Abstract: This paper presents an experimental and numerical investigation of the aerothermal performance of an uncooled winglet tip, under transonic conditions. Spatially resolved heat transfer data, including winglet tip surface and near-tip side-walls, are obtained using the transient infrared thermography technique within the Oxford high speed linear cascade test facility. Computational fluid dynamics (CFD) predictions are also conducted using the Rolls-Royce HYDRA suite. Most of the spatial heat transfer variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Zhang et al [10] reported the detailed experimental evidences of the heat transfer stripe distributions caused by the shock wave structures over the blade tips. Most recently, the overtip choking and shock structures [11] as well as its effects on tip heat transfer [12] were reported by Zhang et al and for even a modern winglet-tip design by O'Dowd et al [13].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Zhang et al [10] reported the detailed experimental evidences of the heat transfer stripe distributions caused by the shock wave structures over the blade tips. Most recently, the overtip choking and shock structures [11] as well as its effects on tip heat transfer [12] were reported by Zhang et al and for even a modern winglet-tip design by O'Dowd et al [13].…”
Section: Introductionmentioning
confidence: 94%
“…However, for cases with strong shock waves, the convergence level becomes worse, but still better than 1×10 -3 . All the 13 results have been checked for convergence by using blade tip surface average heat transfer coefficient monitoring, and the solution is said to be converged when the average heat transfer coefficient is not changed more than 0.05% during 100 successive iterations.…”
Section: Geometry Grid and Boundary Conditionsmentioning
confidence: 99%
“…Only the suction-side squealer with constant width winglet showed heat transfer reduction by 5.5%. O'Dowd et al [31,32] reported transonic heat transfer over a winglet tip without and with cooling, respectively. It has a centerline gutter and a small recessed cavity on the pressure-side overhang.…”
Section: Introductionmentioning
confidence: 98%
“…Saha et al [16] carried out numerical simulations to explore the effect of a pressure-side winglet on flow and heat transfer over a plane, cavity squealer, and suction-side squealer tips. O'Dowd et al [17,18] reported transonic heat transfer over a winglet tip without and with cooling, respectively. It has not only a centerline gutter but also a small recessed cavity on its pressure-side overhang.…”
Section: Introductionmentioning
confidence: 98%
“…It has not only a centerline gutter but also a small recessed cavity on its pressure-side overhang. O'Dowd et al [17] concluded that the turbine blade tip heat transfer is greatly influenced by the shock wave structure inside the tip gap. O'Dowd et al [18] showed that tip Nusselt number increases with coolant injection, and it also increases with increase tip clearance.…”
Section: Introductionmentioning
confidence: 99%